Characterization of Ceiba petandra and Lannea kerstingii Stem Bark Extract Creams - Olusola Isaac Aremu; Adeola Tawakalitu Kola-Mustapha; Taiye Hameedat Ayotunde (Islamic Azad University, 2017)
A study on physicochemical characteristics of Ceiba petandra and Lannea kerstingii stem bark extracts cream being developed for the treatment of topical dermatophytic infections has been carried out to assure safe, effectiveness and stability during storage and usage. The stem barks of Ceiba petandra and Lannea kerstingii were extracted with methanol and ethyl acetate respectively. The obtained extracts and their combinations were formulated into creams using modified Aqueous Cream BP base at concentrations ranging from 0.4 to 3.2%w/w. Physical and chemical characteristics of the creams such as stability, viscosity, pH, diffusion, irritancy and elegance were evaluated. Ketoconazole cream was used as the reference product. Creams prepared with each extract alone exhibited favorable characteristics in terms of spread ability, non-irritancy, stability and diffusivity. Creams formulated with Ceiba petandra were most stable with pH ranges of 6.21 to 7.13. Those formulated Lannea kerstingii were more acidic. Creams formulated with the combinations of the two extracts exhibited some levels of incompatibility, which increased with increasing extract concentrations. The rate of diffusion of the extracts from cream base increased with time and was generally more at 37o C as compared to that at 25o c .Cream formulations of the stem bark extracts of Ceiba petandra and Lannea kerstingii but not their combinations using modified Aqueous Cream (BP) possess satisfactory physicochemical characteristics.